An evaluation of Pancasila student profile strengthening project in vocational schools: Evidence from tangerang district - Ananda Yhuto Wibisono Putra; Sanam Sanam; Hamid Abdillah; Moh Fawaid (Jurnal Pendidikan Vokasi, 2025)
This study aims to evaluate the appropriateness of implementing P5 at SMKN 5 in Tangerang District from the perspectives of context, input, process, and product. The study's findings inform SMKN 5 and other schools that wish to implement P5. The study's participants comprise 91 P5 students who completed a questionnaire, three students who participated in interviews, nine teachers, and three interview informants. This study employs the CIPP (context, input, process, product) evaluation method, a mixed-methods approach with a sequential explanatory design. Data were collected through questionnaires, documentation, interviews, and observations, and analyzed using descriptive statistics. The findings show that: 1) the context is appropriate based on the interviews and observations; 2) the input appropriateness is scored 4.28 (86%) by teachers and 3.81 (76%) by students; 3) the process appropriateness is scored 4.37 (87%) by teachers and 4.16 (83%) by students; 4) the product appropriateness is scored 4.42 (88%) by teachers and 4.27 (85%) by the students; 5) the overall appropriateness is scored 4.36 (87%) by teachers and 4.08 (82%) by students. The evaluation results indicate that the implementation of P5 at SMKN 5 in Tangerang District is considered appropriate. The recommendations include updating the P5 guidelines, developing a holistic evaluation and an interactive teaching method, matching P5 projects to students' competence levels, and enhancing communication with stakeholders.